Clinical standards for diagnosis, treatment and prevention of post-COVID-19 lung disease - Visca D.; Centis R.; Pontali E.; Zampogna E.; Russell A.M.; Migliori G.B.; Andrejak C.; Aro M.; Bayram H.; Berkani K.; Bruchfeld J.; Chakaya J.M.; et al. (International Union Against Tuberculosis and Lung Disease, 2025)
BACKGROUND: The aim of these clinical standards is to provide guidance on ‘best practice’ care for the diagnosis, treatment and prevention of post-COVID-19 lung disease.
METHODS: A panel of international experts representing scientific societies, associations and groups active in post-COVID-19 lung disease was identified; 45 completed a Delphi process. A 5-point Likert scale indicated level of agreement with the draft standards. The final version was approved by consensus (with 100% agreement).
RESULTS: Four clinical standards were agreed for patients with a previous history of COVID-19: Standard 1, Patients with sequelae not explained by an alternative diagnosis should be evaluated for possible post-COVID-19 lung disease; Standard 2, Patients with lung function impairment, reduced exercise tolerance, reduced quality of life (QoL) or other relevant signs or ongoing symptoms ≥4 weeks after the onset of first symptoms should be evaluated for treatment and pulmonary rehabilitation (PR); Standard 3, The PR programme should be based on feasibility, effectiveness and cost-effectiveness criteria, organised according to local health services and tailored to an individual patient’s needs; and Standard 4, Each patient undergoing and completing PR should be evaluated to determine its effectiveness and have access to a counselling/health education session.
CONCLUSION: This is the first consensus-based set of clinical standards for the diagnosis, treatment and prevention of post-COVID-19 lung disease. Our aim is to improve patient care and QoL by guiding clinicians, programme managers and public health officers in planning and implementing a PR programme to manage post-COVID-19 lung disease.